Path Planning for Multiple Mobile Robots in Smart Warehouse - (:unkn) unknown (IEEE, 2019)
Warehouse operations need high labor force and physical space. Currently, companies with huge warehouses are investing on autonomous robots to save time and energy, and to prevent human-based errors. One of the most important challenges in a smart warehouse with multiple moving robots is path planning because of its dynamics. This paper provides a complete and error-free solution to the path-planning problem, and describes its performance in various warehouse scenarios with different number of robots and different design considerations.
Keywords: smart warehouse; mobile robots; path planning